Nasionalisme dan kelas sosial: Ideologi dan praktik partai nasionalis di Indonesia - Retor Kaligis (Masyarakat, Kebudayaan dan Politik, 2014)
This study explores poor people or negative ownership class phenomena as result of exploitative ideology by using power including exploitation of natural resource and placement of population as cheap labor. This study explores poor people or negative ownership class phenomena as result of exploitative ideology by using power, including exploitation of natural resource and placement of human resources as cheaper labor. Although many studies about Indonesian nationalism were conducted previously, but generally the study of nationalism in relation to the poor people class in Indonesia are not the main focus of the study.This article using qualitative research method. In order to compare different phenomena in various periods, this article uses historical comparative research method. There were five levels in historical comparative research. First, is conceptualizing the object of inquiry. Second is locating the evidence. Third is evaluating quality of evidence. Fourth is organizing evidence. Fifth is syntesizing. An open interviewed was conducted with stakeholders whose directly involved in many cases within several political party bodies such as Partai Nasional Indonesia (PNI), Partai Demokrasi Indonesia (PDI). Data was analyzed by social, cultural, and political interpretation. It can be concluded tht in national politic constellation, the phenomena of poor class produce a defense term for their group, known as 'marhaen' and 'wong cilik'. Nevertheless, nationalism practice in Indonesia as represented by PNI, PDI, dan PDI Perjuangan, have not yet succedeed to freed poor people from social aleniation in political power contestation, the ownership of capital, or in relations between state and government. This nation still struggled to build competitive political and economical power in order to reate a social transformation.